Partisipasi Masyarakat Dalam Mewujudkan Gampong Mandiri Di Gampong Suak Puntong - Yulanda Arasih; Reva Dwi Insari; Nodi Marefanda (CV. Ulil Albab Corp, 2022)
The community as one of the subsystems of a village must be involved in the development process in the village. The involvement starts from the development planning stage, implementation, to the supervision stage. This research is entitled